2012
DOI: 10.1519/jsc.0b013e31823a3c54
|View full text |Cite
|
Sign up to set email alerts
|

Primitive Running

Abstract: Running is a sport that has continued to see growth in numbers over the years. Recently, there has been a movement promoting running barefoot and in light, "minimalist" shoes. Advocates of barefoot running believe that a more primitive style of running may result in fewer running-related injuries and even possibly improve performance. To identify the current interest level and participation in barefoot or minimalist shod running, an electronic survey was developed and dispersed to 6,082 runners. The survey ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(33 citation statements)
references
References 12 publications
0
33
0
Order By: Relevance
“…The movement towards barefoot running and minimalist shoes possibly helping with injury prevention, 17 may be transferring over to the weight room without any evidence supporting it. Olympic weightlifting shoes are recommended by the International Weightlifting Federation to protect the lifter’s feet and provide a stable base on the weightlifting platform.…”
Section: Discussionmentioning
confidence: 99%
“…The movement towards barefoot running and minimalist shoes possibly helping with injury prevention, 17 may be transferring over to the weight room without any evidence supporting it. Olympic weightlifting shoes are recommended by the International Weightlifting Federation to protect the lifter’s feet and provide a stable base on the weightlifting platform.…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey, including 364 recreational, 380 competitive, and 41 elite runners participating running races ranging from 5 km to the full marathon, reported that more than 50% of runners had switched from shod running (SR) to running with minimalists (MR) or barefoot running (BR) partially because of their subjective belief in performance enhancement. 3 Since there is a strong linear correlation between the shoe mass and metabolic cost during distance running, 4,5 it has been suggested that reduction of shoe mass during BR or MR may contribute to the improvement in overall running economy compared to SR. In addition, reports suggested the landing pattern may be changed from heelstrike to non-heelstrike during MR or BR, 1,6,7 the energy exchange in MR or BR may thus be more efficient due to the effective mass difference in these two types of landing pattern, 1 and may result in a better running performance.…”
Section: Introductionmentioning
confidence: 99%
“…Many reasons seem to drive people to BF running, however, this popularity is mainly based on the belief that BF alters biomechanical parameters of running, improving impact forces attenuation, increasing performance and reducing injury risk [2,3,58]. …”
Section: Introductionmentioning
confidence: 99%